Granville Leveson-Gower, Marquess of Stafford, correspondence - Stafford, Granville Leveson-Gower, Marquess of, 1721-1803.
ALS written by Stafford to an unknown physician relating to the use of tobacco.
British statesman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Tobacco; Statesmen -- Great Britain